Precarious Property and Violence in the Old Neighborhoods - Gago Prialé, Horacio (2008)
In this paper it been analyzed the possible relation between violence and the lack of property right in the slum areas of the old quarters. It been said that the Law does not just a system of the exercise of coercion, but an order of justice generation which realization is assisted by tools. One of them is the property system. This is a space by which State give support to people to achieve their life goals. In this way, if it would been known the danger that involves the existence of precarious houses and if it would been identify the groups who live there, it would be easy a redefinition of the property rights and an urban renewal. It understood the energy with the violence to explain how it appears in the society. Likewise, it been said that while more efficient and rightful be a normative process that support the property system, the agents will put their effort to find the common good and will be not space for violence. In contrast, when the system does not reflect the reality, the agents will not find officials spaces where they could been accepted and, to the contrary, they will be considered criminals, so the system will penalized them. Later, the author indicates that the situation of an urban conglomerate, for example the case of the Brazilian favelas, institutionalizes a system of a permanent violence. In addition to this, it been said that there were a precariousness process of property which makes the inexistence of the property. The author indicates that the overcoming of this issue does not implies the eradication of the human life in this spaces due to the existent social capital on them support the human life system in the city. On this way, it must generate commitments for the urban renewal. Finally, it been said that the legal system will be capable to eradicate violence and cauterize its lags in the slums, provided that the property right mechanism collect the socio juridical good practices.